Assessment of ICT Resources onboard PCG vessels for Maritime Search and Rescue Operations - Cacao, Leandra M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study evaluates the effectiveness, availability, and efficiency of information and communications technology (ICT) resources onboard Philippine Coast Guard (PCG) vessels to support maritime search and rescue (SAR) operations. It focuses on key ICT components, including data management platforms, navigation tools, communication systems, and human resource capacity. A mixed-methods approach was employed, combining quantitative analysis across different vessel categories with qualitative data from in-depth interviews. Interviews with vessel Commanding Officers and CASB holders provided deeper insight into operational challenges and system limitations. Findings highlight several critical issues: outdated or insufficient ICT equipment, inconsistent connectivity in remote maritime areas, inadequate training on ICT utilization, and the absence of standardized system protocols. Despite these challenges, personnel demonstrated strong appreciation for technological improvements and a clear understanding of ICT’s importance in mission success To enhance the PCG’s SAR capabilities, the study recommends upgrading onboard ICT systems, establishing standardized operating procedures, and strengthening technical training. Ultimately, improving ICT infrastructure and personnel readiness is essential to boosting response effectiveness and ensuring the safety of lives and property during maritime emergencies.